Engineering the secretome of Aspergillus niger for cellooligosaccharides production from plant biomass - de Figueiredo, Fernanda Lopes; Contesini, Fabiano Jares; Terrasan, César Rafael Fanchini; Gerhardt, Jaqueline Aline; Corrêa, Ana Beatriz; Antoniel, Everton Paschoal; Wassano, Natália Sayuri; Levassor, Lucas; Rabelo, Sarita Cândida [UNESP]; Franco, Telma Teixeira; Mortensen, Uffe Hasbro; Damasio, André (Springer Nature, 2024)
Background: Fermentation of sugars derived from plant biomass feedstock is crucial for sustainability. Hence, utilizing customized enzymatic cocktails to obtain oligosaccharides instead of monomers is an alternative fermentation strategy to produce prebiotics, cosmetics, and biofuels. This study developed an engineered strain of Aspergillus niger producing a tailored cellulolytic cocktail capable of partially degrading sugarcane straw to yield cellooligosaccharides. Results: The A. niger prtT∆ strain created resulted in a reduced extracellular protease production. The prtT∆ background was then used to create strains by deleting exoenzyme encoding genes involved in mono- or disaccharide formation. Consequently, we successfully generated a tailored prtT∆bglA∆ strain by eliminating a beta-glucosidase (bglA) gene and subsequently deleted two cellobiohydrolases and one beta-xylosidase encoding genes using a multiplex strategy, resulting in the Quintuple∆ strain (prtT∆; bglA∆; cbhA∆; cbhB∆; xlnD∆). When applied for sugarcane biomass degradation, the tailored secretomes produced by A. niger resulted in a higher ratio of cellobiose and cellotriose compared with glucose relative to the reference strain. Mass spectrometry revealed that the Quintuple∆ strain secreted alternative cellobiohydrolases and beta-glucosidases to compensate for the absence of major cellulases. Enzymes targeting minor polysaccharides in plant biomass were also upregulated in this tailored strain. Conclusion: Tailored secretome use increased COS/glucose ratio during sugarcane biomass degradation showing that deleting some enzymatic components is an effective approach for producing customized enzymatic cocktails. Our findings highlight the plasticity of fungal genomes as enzymes that target minor components of plant cell walls, and alternative cellulases were produced by the mutant strain. Despite deletion of important secretome components, fungal growth was maintained in plant biomass.
Keywords: Aspergillus niger; CAZymes; Cellooligosaccharides; Fungal engineering; Sugarcane biomass; Tailor-made enzymatic cocktail